The Role of Brand Trust in Mediating the Negative Influence of E-WOM and Content Marketing on Repurchase Intention (Case Study of Tomoro Coffee Seminyak) - Anak Agung Putu Aditya Parma; Ida Ayu Iswari Pidada (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid growth of Tomorro Coffee in Indonesia, especially in the Seminyak area, occurs amidst high consumer digital activity influenced by online reviews and content marketing. This study aims to examine the influence of Negative Electronic Word of Mouth (Negative E-WOM) and Content Marketing on Repurchase Intention with Brand Trust as a mediating variable. This study focuses on Tomoro Coffee Seminyak consumers who are actively involved in digital interactions and have made repeat purchases. A quantitative approach was used in this study using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method to analyze the relationship between variables. The results show that Negative E-WOM and Content Marketing have a significant effect on Brand Trust and Repurchase Intention. In addition, Brand Trust is proven to have a significant effect on Repurchase Intention and mediates the relationship between Negative E-WOM and Content Marketing on Repurchase Intention. Overall, these findings indicate that consumers' repeat purchase decisions are more influenced by digital perceptions and their level of trust in the brand than by offline experience factors alone. The implications of this research emphasize that companies need to strengthen their digital communication strategies and manage consumer trust to increase repeat purchase intentions.